Use of emotions in the post of the candidates in the Peruvian elections 2016 - Cohaila, Edwin (2020)
The article analyzes the publications (post) of the presidential candidates in the 2016 Peruvian elections, through a content analysis. It has proceeded to make a capture of publications (post) that show some emotion in a period of fourteen days before the elections, both in first and second round. It can be seen that the candidates have little use of emotions, and that their recurrence is associated with expressing positive emotions over negative ones, not highlighting the search for confrontation with another candidate; also, a certain pattern is observed in the use of emotions but only in the case of female candidates.